Diversity of Molluscs Associated with Mangroves on The Gerupuk Beach in Central Lombok in 2023 - Jennifer Isabelana Dasilva; Abdul Syukur; Mahrus Mahrus (Jurnal Biologi Tropis, 2023)
Mangrove ecosystems have an important role in coastal areas. One of the roles of mangroves is to protect the shoreline and prevent seawater intrusion. Molluscs are one of the mangrove association biota whose lives are influenced by the presence of mangrove forests. Therefore, the purpose of this study was to determine the diversity of molluscs and the relationship between mangrove density and limiting molluscs to the coastal mangrove area of ​​Gerupuk Beach, Central Lombok. Sampling of molluscs used the quadrate sampling method with purposive sampling by taking into account the mangrove species found in the observation plots. The data obtained were then analyzed with the charisma index, associations, and Pearson's correlation coefficient. The results of this study obtained 13 species of Molluscs consisting of 12 species of the Gastropod family and 1 species of the Bivalvia family. The Brachyura diversity index at the research station was moderate with a value between 1.48–1.88. Furthermore, there were 8 species of Molluscs associated with 4 species of mangrove from 13 species of Molluscs found. The linear regression equation y = 0.1429x + 0.0007 with a Pearson correlation coefficient (r) of 0.57 indicates a strong relationship between the independent variable (x) mangrove density and the dependent variable (y) exposure to molluscs. The conclusion of this study is that the diversity of molluscs in the mangrove area of ​​Gerupuk Beach is included in the moderate category and there is a significant relationship between mangrove density and mollusk attractions.